Penggunaan Kata dan Frase ’Tidak Baku’ dalam Bidang Fotografi - Zulisih Maryani (Rekam: Jurnal Fotografi, Televisi, Animasi)
The purpose of this study is to describe the use of words and phrases'non-standard' in the field of photography are presented along withjustification. In addition, the purpose of this study is also to describe thefactors causing the writing of words and phrases' non-standard in the fieldof photography.This research used descriptive method with three stages, namely datacollecting stage, data analysis stage, and result data analysis presentationstage. Data collecting stage was conducted by observing the language used in words and phrases ‘non-standard’ in the field of photography. Observing was continued with the recording technique. Data analysis was conducted after the collected data had been classified. The analysis applied was describing the use of words and phrases 'non-standard' in the field of photography are presented along with justification and describing the factors causing the writing of words and phrases' non-standard in the field of photography. The presentation of result data analysis was presented in the informal and formal. The informal presentation of result data analysis used common words and the formal used tables.Words and phrases 'non-standard' in the field of photography is thepronunciation of words and phrases or writing does not meet standardnorms or rules that have been standardized. The words are classified asnon-standard should be avoided in formal situations or in writing scientificpapers, for example body kamera, diafrakma, detil foto, foto candit, fotoessay, fotogravi, fotografi portrait, monopot, pas photo, and tripot. Thatwords should be written bodi kamera, diafragma, detail foto, foto candid,foto esai, fotografi, fotografi potret, monopod, pasfoto, and tripod.The factors causing the writing of words and phrases' non-standard inthe field of photography include (1) the influence of foreign languages,2 especially English, (2) ignorance of the rules EYD (writing standard wordsand standard terms), and (3) the influence of non-standard pronunciation.